Crack constitutive model for the prediction of punching failure modes of fiber reinforced concrete laminar structures - Barros, Joaquim A. O. (2011)
The capability of a multi-directional fixed smeared crack constitutive model to simulate the flexural/punching failure modes of fiber reinforced concrete (FRC) laminar structures is discussed. The constitutive model is implemented in a computer program based on the finite element method, where the FRC laminar structures were simulated according to the Reissner-Mindlin shell theory. The shell is discretized into layers for the simulation of the membrane, bending and out-of-plane shear nonlinear behavior. A stress-strain softening diagram is proposed to reproduce, after crack initiation, the evolution of the normal crack component. The in-plane shear crack component is obtained using the concept of shear retention factor, defined by a crack-strain dependent law. To capture the punching failure mode, a softening diagram is proposed to simulate the decrease of the out-of-plane shear stress components with the increase of the corresponding shear strain components, after crack initiation. With this relatively simple approach, accurate predictions of the behavior of FRC structures failing in bending and in shear can be obtained. To assess the predictive performance of the model, a punching experimental test of a module of a façade panel fabricated with steel fiber reinforced self-compacting concrete is numerically simulated. The influence of some parameters defining the softening diagrams is discussed.